Marketing Policy for Micro, Small, and Medium Enterprises Products After the COVID-19 Pandemic in Sontang Village, Bonai Darussalam District, Rokan Hulu Regency, Riau Indonesia (Study: Salai Fish Products (Smoked Fish)) - Nurman Nurman; Hamsal Hamsal; Mashur Fadli (Quantitative Economics and Management Studies, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are economic businesses carried out by the lower middle class. This business aims to grow and develop its business to support efforts to reduce poverty and poverty and provide new job opportunities. In general, there are three (3) types of businesses that include MSMEs, namely (1) culinary businesses, (2) fashion businesses, and (3) agribusiness businesses. Making salai fish is a culinary business. The raw materials from fishermen's catches are then processed into the final product, which has added value. The object of this study is marketing policies ranging from products, prices, and distribution to promotions. The results showed that procedures in the field of production if you want to increase the income of the production process are carried out twice a week, policies in the area of prices depend on the high low purchasing power of end consumers, policies in the place of distribution try to shorten distribution channels because the longer the distribution channel affects income, and procedures in the business of promotion if the interest of end consumers decreases, it is thought that it is necessary to collaborate with partners such as houses eating, self-service and other services, expanding the market can be done by communicating, increasing selling places and increasing promotions by utilizing online media so that any product produced is sold out, and it is also suggested to MSME entrepreneurs to start cultivating river fish for the long term of the salai fish business